Stress-relaxation ageing behavior and microstructural evolution under varying initial stresses in an Al–Cu alloy: Experiments and modeling. (April 2020) - Yang, Youliang; Zhan, Lihua; Liu, Chunhui; Wang, Xun; Wang, Qing; Tang, Zhimao; Li, Guopeng; Huang, Minghui; Hu, Zhenggen
Abstract: Complex curvature and/or high-stiffened components are often in the elastic-plastic deformation range during the loading stage of creep age forming (CAF) process. Effects of initial stress level, extending from 80 to 210 MPa (typically experienced by large-scale structural components), on the stress relaxation ageing behavior and microstructural evolution of AA2219 alloy have been experimentally investigated by means of stress relaxation ageing tests, tensile tests and scanning transmission electron microscopy. Stress relaxation curves can be mainly divided into two stages: the variable-rate relaxation (VRR) stage and steady-rate relaxation (SRR) stage. When the initial stress levels are less than the yield strength, all stress relaxation curves exhibit a similar decreasing tendency where the stress reduces rapidly in a short VRR stage and then remains almost unchanged for a long SRR stage. Distinctively, the stress relaxation curve whose initial stress is higher than yield strength does not experience the same relaxation law. With increasing initial stress, the duration of the VRR stage extends appreciably and the stress reduction rate during the SRR stage increases. Stress exponent calculation considering the threshold stress suggests the dislocation creep mechanism governs the deformation of stress relaxation. Dislocations induced by loading initial stress are responsible for the significant difference in stress relaxation behavior for different initial stress levels. Besides, age strengthening effect improves with increase in initial stress, as is ascribed to the enhanced precipitation of pre- θ ' and θ ' phases accompanying conventional GP zones and θ ″ . A straightforward, mechanism-based constitutive modeling is established by considering the dislocation and threshold stress. The material constants are calibrated using the experimental data. The initial-stress-level dependence of stress relaxation behavior predicted through the derived constitutive modeling agrees well with the experimental results. The proposed constitutive modeling can be applied to accurately simulate the CAF of large complex structural parts. Graphical abstract: Image 1 Highlights: The unique cross-over characteristics of stress relaxation curves for different initial stress levels are identified. GP II zones, pre- θ ' and θ ' phases are responsible for strengthening mechanism at high-initial-stress regime. The significant difference in stress relaxation behavior is attributed to the dislocations generated at the loading stage. Threshold stress for stress relaxation behavior is related with the initial stress level and loading-induced dislocations. A dislocation based constitutive model is established to describe the initial-stress-dependent stress relaxation behavior.